Effect of Treatment with a Natural Extract of Mukdenia Rossii (Oliv) Koidz and Unipolar Ion Emission on the Antibacterial Performance of Air Filters - Lee, Dae Hee; Jung, Jae Hee; Lee, Byung Uk (TAIWAN ASSOC AEROSOL RES-TAAR, 2013)
Airborne microorganisms are deposited on air filters when these are used to reduce aerosol concentrations in indoor environments. These microorganisms cause various undesirable effects, such as production of unpleasant odors and re-suspension of bacterial and fungal spore bioaerosols into the indoor air. To resolve these issues, we investigated the antimicrobial effects of a natural extract of Mukdenia rossii (Oliv) Koidz and unipolar ion emission against bioaerosols deposited on air filters. The experimental results showed that the natural extract had an antimicrobial effect on the deposited bioaerosols, and that unipolar ion emission enhanced the antimicrobial performance of the natural extract.
Keywords: INACTIVATION; EPIDERMIDIS; PARTICLES; SUBTILIS; REMOVAL